Internationalization in Higher Education: Critical Reflections on Its Conceptual Evolution - de Wit, Hans (International Higher Education, 2023)
Internationalization is a multifaceted and evolving phenomenon, and its theories and definitions continue to be adjusted to match new and evolving understandings. Given the current complicated global environment, it is important to challenge past mostly market-oriented perceptions, and define relevant new directions for internationalization in higher education.